Sterile alpha and TIR motif-containing protein 1 is a negative regulator in the anti-bacterial immune responses in nile tilapia (Oreochromis niloticus) - Trung, Nguyen Bao; Nguyen, Tan-Phat; Hsueh, Hao-Yun; Loh, Jiun-Yan; Wangkahart, Eakapol; Wong, Alice Sui Fung; Lee, Po-Tsang (Frontiers in Immunology, 2022)
Nile tilapia (Oreochromis niloticus) is one of the most important food fish in the world. However, the farming industry has encountered significant challenges, such as pathogen infections. Toll-like receptors (TLRs) play an essential role in the initiation of the innate immune system against pathogens. Sterile alpha and TIR motif-containing protein 1 (SARM1) is one of the most evolutionarily conserved TLR adaptors, and its orthologs are present in various species from worms to humans. SARM1 plays an important role in negatively regulating TIR domain-containing adaptor proteins inducing IFNβ (TRIF)-dependent TLR signaling in mammals, but its immune function remains poorly understood in fish. In this study, O. niloticus SARM1 (OnSARM1) was cloned and its evolutionary status was verified using bioinformatic analyses. mRNA expression of OnSARM1 was found at a higher level in the trunk kidney and muscle in healthy fish. The examination of its subcellular location showed that the OnSARM1 was detected only in the cytoplasm of THK cells, and colocalized with OnMyD88, OnTRIF and OnTRIF in small speckle-like condensed granules. The transcript levels of OnMyD88, OnTIRAP, OnTRIF, and downstream effectors, including interleukin (IL)-1β, IL-8, IL-12b and type I interferon (IFN)d2.13, were regulated conversely to the expression of OnSARM1 in the head kidney from Aeromonas hydrophila and Streptococcus agalactiae infected fish. Moreover, the treatment of THK cells with lysates from A. hydrophila and S. agalactiae enhanced the activity of the NF-κB promoter, but the effects were inhibited in the OnSARM1 overexpressed THK cells. Overexpression of OnSARM1 alone did not activate the NF-κB-luciferase reporter, but it suppressed OnMyD88- and OnTIRAP-mediated NF-κB promoter activity. Additionally, OnSARM1 inhibited the mRNA expression of proinflammatory cytokines and hepcidin in A. hydrophila lysate stimulated THK cells. Taken together, these findings suggest that OnSARM1 serves as a negative regulator by inhibiting NF-κB activity, thereby influencing the transcript level of proinflammatory cytokines and antimicrobial peptides in the antibacterial responses.